Risk Of Zoonotic Diseases Transmission From Indian Flying Foxes To Humans, Domestic Animals And Wild Fauna In District Poonch., Jammu And Kashmir, India - R.L Bhellum; Punica; Ruchika Sharma (International Journal of Pharma and Bio Sciences, 2020)
Indian flying foxes have been considered to be playing a serious role in transmission of infectious diseases, especially the zoonotic ones in District Poonch among human humans and animals. The District Poonch is a far flung area. It has not been explored in respect of diseases being transmitted as yet. Over 4500 Indian flying foxes are roosting from last many years in Poonch town. During continuous stay for the last many years in Poonch, Authors have collected information from literature, informants, medical /animal husbandry departments and many others senior citizens ofPoonch. In the past two decades, several high impact of zoonotic diseases outbreak have been linked to bat borne viruses and animals origin have been reported. The bat bat born infections are SARS, corona virus, Hendra virus, Nipah virus and many others. Hence, it is accepted that Ebola viruses, MERS, Corona etc. linked to bats. Bats are potential reservoir of large number of known and unknown disease viruses / organisms, most of which could spill over to humans and animals about which people in normal life don’t have much knowledge. Seventy five per cent infectious diseases are Zoonotic. So, the residents living around conservation area mostly had poor knowledge about flying foxes and disease transmission. It has been seen from result of information collected within limited area conservation of(50 residents) from within 1 km, from 1-5kms and 5-10kms byinterviewing participants. This shows that the people animals in this region is at quite high risk of contracting infectious diseases from flying foxes and others animals etc. that needs to be taken care of since the matter of public health importance.